2005
DOI: 10.1897/04-081r.1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of select antidepressants in fish from an effluent‐dominated stream

Abstract: Increasing evidence indicates widespread occurrence of pharmaceuticals and personal care products (PPCPs) in municipal effluent discharges and surface waters. Studies that characterize the fate and effects of PPCPs in aquatic systems are limited, and to our knowledge, data regarding pharmaceutical accumulation in fish of effluent-dominated ecosystems have not been previously reported. In the present study, fish populations were sampled from a reference stream and an effluent-dominated stream in north Texas, US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

25
249
7
8

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 489 publications
(289 citation statements)
references
References 27 publications
25
249
7
8
Order By: Relevance
“…Brooks et al [7] then identified bioaccumulation of selective serotonin reuptake inhibiting (SSRI) antidepressants by fish from an effluent-dominated stream in north Texas, USA. These antidepressants were targeted for study because of high volume of distribution (V D ) values, elevated lipophilicity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Brooks et al [7] then identified bioaccumulation of selective serotonin reuptake inhibiting (SSRI) antidepressants by fish from an effluent-dominated stream in north Texas, USA. These antidepressants were targeted for study because of high volume of distribution (V D ) values, elevated lipophilicity (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In some species of vertebrates, PBDEs alter thyroid function, reduce sperm counts, and delay sperm maturation by interfering with androgen synthesis (Kuriyama et al, 2005). Contaminants of emerging concern (CECs), which include PBDEs, are present in many waters of the U.S. (Kolpin et al, 2002;Focazio et al, 2008), including effluent reaching the Columbia River (Morace, 2012) and in sediments of the LCR , and some of those compounds accumulate in fish tissue (Brooks et al, 2005;Ramirez et al, 2009;Schultz et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some antibiotics, particularly quinolones, can bioaccumulate at relatively high levels in molluscs (Li et al 2012). Anti-depressants were also found to bioaccumulate in periphyton, snails (Du et al 2015), benthic invertebrates (Grabicova et al 2015), bivalves (Bringolf et al 2010) and the muscles of fish species used for human consumption (Brooks et al 2005). It should be noted that some APIs may easily be transferred through the trophic route, although their bioaccumulation in fish may be low due to efficient liver metabolism.…”
Section: Fate Of Pharmaceuticals In the Freshwater Environmentmentioning
confidence: 99%